Interleukin‐36 in hidradenitis suppurativa: evidence for a distinctive proinflammatory role and a key factor in the development of an inflammatory loop. (1st March 2018) - Hessam, S.; Sand, M.; Gambichler, T.; Skrygan, M.; Rüddel, I.; Bechara, F.G.
Summary: Background: Possible regulatory involvement of the interleukin (IL)‐36 family in inflammatory diseases has been suggested. Objectives: To analyse the expression of IL‐36α, IL‐36β, IL‐36γ and the antagonistic cytokines IL‐36 receptor agonist (IL‐36Ra), IL‐37 and IL‐38 in the skin of patients with hidradenitis suppurativa (HS). Methods: Skin samples from lesional and corresponding perilesional HS skin, and from healthy controls were included in this study and analysed by quantitative real‐time reverse‐transcriptase polymerase chain reaction (PCR). To evaluate the PCR results of IL‐36α, IL‐36β and IL‐36γ, a subset of skin samples was studied by immunohistochemistry. Results: Expression levels of IL‐36α, IL‐36β, IL‐36γ and IL‐36Ra were all significantly higher in lesional HS skin than in healthy controls. IL‐37 and IL‐38 levels were significantly higher in perilesional HS skin than in healthy controls and were decreased in lesional HS skin. Limitations of the study are its descriptive nature and the small sample size. Conclusions: Our results showed a possible involvement of IL‐36 cytokines in the inflammatory network of HS and a dysbalance between the agonistic and antagonistic cytokines in HS skin.